2018
DOI: 10.1016/j.yhbeh.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between estrogen receptors and metabotropic glutamate receptors and their impact on drug addiction in females

Abstract: Contribution to Special Issue on Fast effects of steroids. Estrogen receptors α and β (ERα and ERβ) have a unique relationship with metabotropic glutamate receptors (mGluRs) in the female rodent brain such that estradiol is able to recruit intracellular G-protein signaling cascades to influence neuronal physiology, structure, and ultimately behavior. While this association between ERs and mGluRs exists in many cell types and brain regions, its effects are perhaps most striking in the nucleus accumbens (NAc). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 139 publications
(161 reference statements)
5
45
0
Order By: Relevance
“…Note: AR, androgen receptor; BNST, bed nucleus of the stria terminalis; ER-alpha, estrogen receptoralpha; ER-beta, estrogen receptor-beta; GABA, gamma-aminobutyric acid; GR, glucocorticoid receptor; HPA, hypothalamic-pituitary-adrenal; mPFC, medial prefrontal cortex; MR, mineralocorticoid receptor; PR, progesterone receptor (both isoforms); PVN, paraventricular nucleus; VTA, ventral tegmental area. Source: Circuitry 13,24 and steroid receptor distribution 13,15,21,[33][34][35][36] are modified from other sources.…”
Section: Steroid Hormone Receptors and Circuitry Important For Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Note: AR, androgen receptor; BNST, bed nucleus of the stria terminalis; ER-alpha, estrogen receptoralpha; ER-beta, estrogen receptor-beta; GABA, gamma-aminobutyric acid; GR, glucocorticoid receptor; HPA, hypothalamic-pituitary-adrenal; mPFC, medial prefrontal cortex; MR, mineralocorticoid receptor; PR, progesterone receptor (both isoforms); PVN, paraventricular nucleus; VTA, ventral tegmental area. Source: Circuitry 13,24 and steroid receptor distribution 13,15,21,[33][34][35][36] are modified from other sources.…”
Section: Steroid Hormone Receptors and Circuitry Important For Stressmentioning
confidence: 99%
“…For instance, estradiol and progesterone can rapidly affect dopamine signaling via actions at their respective steroid receptors, functional coupling between estrogen receptors (both alpha and beta) and metabotropic glutamate receptors (Group I or Group II) can activate distinct signaling pathways, and neurosteroids can rapidly increase GABA A receptor-mediated signaling. 21,23,24,[33][34][35][36] Thus, rapid steroid actions at associated receptors and neurosteroid actions at GABA A receptors are other mechanisms for fine-tuning central nervous system excitability.…”
Section: Steroid Hormone Receptors and Circuitry Important For Stressmentioning
confidence: 99%
“…We used selective agonists and antagonists to ERa and ERb combined with extracellular recordings of VTA DA neurons. Because membrane-bound estrogen receptors can rapidly activate cell signaling pathways through interactions with metabotropic glutamate receptors (mGluRs) and affect neurotransmission and behavior (Tonn Eisinger et al, 2018), the second goal of this study was to determine if the enhancement of ethanol-stimulated VTA DA neuron firing by E2 is dependent on mGluR1 activity.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen, progestin, and androgen signaling in the brain is involved in the display of motivated behaviors such as copulation, aggression, and physical activity (Beatty, 1979). Moreover, gonadal hormones have been shown to influence the susceptibility to addiction-like behavior (Tonn Eisinger et al, 2018a). In order to understand how hormones affect behavior, it is important to study the underlying neurobiological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that spine density, spine morphology, and dendrite length can be impacted by gonadal hormones in multiple brain regions involved in motivation (Calizo and Flanagan-Cato, 2002;Cooke and Woolley, 2005;Cunningham et al, 2007;Peterson et al, 2015). These hormone-induced structural reorganizations are both sexually dimorphic and strikingly different between brain regions, and have been linked to motivated behavior, learning, memory, and addiction (Frankfurt and Luine, 2015;McEwen and Milner, 2017;Tobiansky et al, 2018;Tonn Eisinger et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%